Comparative Assessment of Depression Level Among Polytechnic Staff - A., Adetunji A.; J., Olajide B.; J., Onemayin K. (EDUMALSYS Journal of Research in Education Management, 2026)
This study investigates the prevalence and variation of depressive symptoms across staff categories in two polytechnics in the southwestern part of Nigeria, against a backdrop of workplace stress, job insecurity, workload, and institutional pressures that threaten employee well-being. Adopting a cross-sectional survey design, the research employs standardized psychological instruments, specifically the Beck Depression Inventory (BDI), to assess depressive symptoms among academic and non-academic staff. Data collected from respondents were analyzed using descriptive statistics and inferential tests, including t-tests and ANOVA, to identify significant sociodemographic variables associated with depression levels. The findings indicate varying degrees of depression, with non-academic staff exhibiting higher levels of depressive symptoms, influenced by job roles, support systems, and workload. Male staff are significantly more depressed than female staff, while those aged 30–49 years also show higher levels of depression, and Christian respondents emerge as the most depressed among the examined religious groups. The study concludes that depression among polytechnic staff is differentially distributed across staff categories and sociodemographic groups, underscoring the importance of institutional mental health policies and proactive interventions to foster a healthier and more productive workforce. It recommends the implementation of regular mental health screenings, workplace counselling services, and targeted support programs to address identified vulnerabilities and promote staff well-being.